(untitled) (Baghdad Science Journal, 2025)
Polyvinal alcohol was Cynoethylated , complex compound with Iodin in presence of Cu++ ions were preparated and their ultra violet (U.V) and infra red( IR) spectra were investigated. The prepared derivative and complexes were evaluated as antibacterial and antifungal agents following the standard dilution method. MIC(minimum inhibitory concentration) for each polymer using ten types of gram + ve and gram _ ve bacteria were determinated in addition to three types of fungi. The results obtainded showed that MIC, s were around 0.0011 × 103 molar for different polymetric derivatives tried.